Taxonomic review of the genus Phrynocaria Timberlake, 1943 (Coleoptera: Coccinellidae) from China with description of a new species - Zhu, Zi-Hao; Wang, Zi-Zhao; Shi, Ai-Min; Wang, Xing-Min (Zootaxa, 2026)
The genus Phrynocaria Timberlake from China is reviewed. Six species of Phrynocaria are reported, described and illustrated, including one new species P. bella Zhu & Wang sp. nov. A key and a distribution map of the known species are also presented.